Von Willebrand factor propeptide in severe coronavirus disease 2019 (COVID-19): evidence of acute and sustained endothelial cell activation - Ni Cheallaigh, Cliona; Martin-Loeches, Ignacio (My University, 2021)
Endothelial cell (EC) activation plays a key role in the pathogenesis of pulmonarymicrovascular occlusion, which is a hallmark of severe coronavirus disease 2019(COVID-19). Consistent with EC activation, increased plasma von Willebrand factorantigen (VWF:Ag) levels have been reported in COVID-19. Importantly however,studies in other microangiopathies have shown that plasma VWF propeptide(VWFpp) is a more sensitive and specific measure of acute EC activation. In the pre-sent study, we further investigated the nature of EC activation in severe COVID-19.Markedly increased plasma VWF:Ag [median (interquatile range, IQR) 608 8 (531–830)iu/dl] and pro-coagulant factor VIII (FVIII) levels [median (IQR) 261 9 (170–315) iu/dl] were seen in patients with severe severe acute respiratory syndrome coro-navirus-2 (SARS-CoV-2) infection. Sequential testing showed that these elevatedVWF–FVIII complex levels remained high for up to 3 weeks. Similarly, plasmaVWFpp levels were also markedly elevated [median (IQR) 324 6 (267–524) iu/dl].Interestingly however, the VWFpp/VWF:Ag ratio was reduced, demonstrating thatdecreased VWF clearance contributes to the elevated plasma VWF:Ag levels in severeCOVID-19. Importantly, plasma VWFpp levels also correlated with clinical severityindices including the Sequential Organ Failure Assessment (SOFA) score, Sepsis-Induced Coagulopathy (SIC) score and the ratio of arterial oxygen partial pressure tofractional inspired oxygen (P/F ratio). Collectively, these findings support thehypothesis that sustained fulminant EC activation is occurring in severe COVID-19,and further suggest that VWFpp may have a role as a biomarker in this setting
PUBLISHED
cited By 6
Keywords: Endothelial cell (EC); von Willebrand factorantigen (VWF:Ag); Sequential Organ Failure Assessment (SOFA) score; Endothelial cell (EC); von Willebrand factorantigen (VWF:Ag); Sequential Organ Failure Assessment (SOFA) score